2016
DOI: 10.1073/pnas.1603192113
|View full text |Cite
|
Sign up to set email alerts
|

Compartment and signal-specific codependence in the transcriptional control of Salmonella periplasmic copper homeostasis

Abstract: Copper homeostasis is essential for bacterial pathogen fitness and infection, and has been the focus of a number of recent studies. In Salmonella, envelope protection against copper overload and macrophage survival depends on CueP, a major copper-binding protein in the periplasm. This protein is also required to deliver the metal ion to the Cu/Zn superoxide dismutase SodCII. The Salmonella-specific CueP-coding gene was originally identified as part of the Cue regulon under the transcriptional control of the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…). This was expected for a gene controlled by GolS (Checa et al ., ; Pontel et al ., ) because it requires the metal‐activated regulator to initiate transcription (Pezza et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…). This was expected for a gene controlled by GolS (Checa et al ., ; Pontel et al ., ) because it requires the metal‐activated regulator to initiate transcription (Pezza et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…), suggesting that, besides GesABC pump, other factors under CpxR/CpxA‐control are involved in handling the stress caused by the toxic metal at the cell envelope. A similar effect has been previously reported when testing the sensitivity to copper, another group IB metal from the periodic table with similar physicochemical properties than Au, that severely impacts the cell envelope (Yamamoto and Ishihama, ; Pezza et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Pezza et al . ). Abbreviations: MCO , multicopper oxidases; RND , resistance nodulation cell division.…”
Section: Mechanisms Of Microbial Copper Resistancementioning
confidence: 97%
“…It has been shown that CueP expression is controlled by a CueR‐like ‘activator‐type’ which can detect an increase in cytoplasmic concentration of copper using the two‐component system CpxR/CpxA when stress is detected at the bacterial membrane level (Pezza et al . ).…”
Section: Mechanisms Of Microbial Copper Resistancementioning
confidence: 97%